Impacts of Rural Community on the Forest Estate in Ugbolu, Oshimili North Local Government Area, Delta State, Nigeria - Ohwo, Oghenekevwe Abigail; Nzekwe-Ebonwu, Nnamdi Francis (Journal of Forests, 2021)
This study examined the impact of Community based forest management (CBFM) in Ugbolu forest reserve (UFR), Delta State. A random selection of 110 respondents was carried out. Information on activities encouraging deforestation, list of resources extracted, jobs and income provided from involvement in CBFM, structure and strategy used by community in managing UFR were collected using structured questionnaire and interview section. Descriptive statistics was used to analysed the data (frequency table and likert scale). Majority of respondents were male (51.8%), married (61.6%), between the age of 31-40 (34.5%), had household size of 7-9 (39.1%). The activities that contributed to deforestation in the reserve were logging (70.9%), livestock breeding (15.5%), and farming (10.9%). The forest resources harvested included Tectona grandis, Gmelina aborea, Rattus fuscipes, Thryonomy swinderianus. Involvement in CBFM provided jobs (categorized as Forest user groups (FUG) namely; timber merchants, fellers, loaders, hunters, farmers, forest guards to community members. The income earned varied between ₦11,000 (28.9) to ₦200,000 (526.3) monthly. Majority (58.2%) of respondent stated that heads of different FUG constituted the committee which works with an annual plan (53.4%), arrived at by voting (70.0%). The annual plans meet the demands of various FUG (81.8%) with little interference from government (86.4%). The committees major forest management strategies included partnership of forest guards with rural people (40.0%), creation of a community forest administration group (26.4%) and laws stopping illegal entry into the forest estate (23.4%). Intensification of government involvement and adequate funding for effective CBFM were recommended by the study.